عصری سماجی علوم کی اسلام کاری کی ضرورت : درپیش چیلنجزاور اسلام کاری کی حکمتِ عملی: The Need for Islamization of Modern Social Sciences: The Challenges and Strategies for Islamization (Al-Qamar, 2019)
Knowledge belongs to various fields, which discuss the social, political, natural and material aspects of any society. There are two theories about social sciences; Islamic Theory and Secular or Western Theory. These theories reflect the social background of any society. Ethical values carry primary importance in educational system. With their development, contemporary social sciences have laid huge impact on not only non-Muslim individuals, but some Muslim intellectuals have also fallen prey to their sententious impact. In result, Muslim scholars feel proud after getting educated from contemporary social sciences. But, being devoid of spiritual impact, contemporary social sciences have led them to the way where neither God has any place nor the ethical values have any importance. Since the importance of contemporary social sciences, in current scenario, cannot be denied, the Muslim scholars and intellectuals have shown serious concern in this matter. They have different view points on whether the Muslims should derivate and utilize the contemporary social sciences or not. There has been a lot of debate and discussion on the issue of Islamization of modern social sciences among the Muslim intellectuals also.  This article aims at the need and challenges being faced in Islamizing contemporary social sciences. The discussion will be made on how the unislamic elements of contemporary social sciences can be Islamized.
Keywords: Education; Islamization; Knowledge; Social Sciences